Experimental study on mitigation of earthquake hazard using rubber - soil mixture - Göztepe, Barış. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Seismic isolation systems have been developed in order to improve seismic performance of structures. Geotechnical seismic isolation systems as an alternative method for improving seismic performance of structures have been proposed, recently. In geotechnical seismic isolation system, earthquake e ects transferred from ground to structure are decreased using geotechnical techniques and materials. One of materials proposed as geotechnical seismic isolator is Rubber-Soil Mixtures (RSM) because of material properties advantages such as low unit weight, low bulk density, high drainage capacity and high vibration absorption capacity. The objective of this thesis is to determine the e ectiveness of the proposed RSM method on the seismic performance of low-to-medium rise buildings by shake table experiments. 1/10 scaled 3 and 5 story building models were designed and constructed in order to determine the e ects of RSM as a geotechnical seismic isolation material. The shake table experiments were performed with di erent rubber types, di erent rubber contents for RSM and di erent RSM thickness under selected seismic motions. The seismic performance of the proposed seismic isolation method was compared with the non-isolated models. This comparative study shows that rubber soil mixtures have considerable positive e ects on mitigation of earthquake hazards. Surrounding the foundation of buildings by rubber soil mixture is an e ective solution to dissipate earthquake energy, thus reducing the response of a structure and minimizing potential damage under earthquake excitation.
Keywords: Waste tires.; Waste products as building materials.; Earthquake resistant design -- Mathematical models.; Buildings -- Earthquake effects.